Enabling Urban Alternatives Crises, Contestation, and Cooperation - Fisker, Jens Kaae.; Chiappini, Letizia; Pugalis, Lee.; Bruzzese, Antonella; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book asks how thinking, governing, performing, and producing the urban differently can assist in enabling the creation of alternative urban futures. It is a timely response to the ongoing crises and pressing challenges that inhabitants of cities, towns, and villages worldwide are faced with in the midst of what has been widely dubbed as 'an urban age'. Starting from the premise that current urban development patterns are unsustainable in every sense of the word, the book explores how alternative patterns can be pursued by the wide variety of actors - from governments and international institutions to slum-dwellers and social movements - involved in the on-going production of our shared urban condition. The challenges addressed include exclusion and segregation; persisting poverty and increasing inequality; urban sprawl and changing land use patterns; and the spatial frames of urban policy. As such the book appeals to urban scholars, policy makers, activists, and others concerned with shaping the future of our cities and of urban life in general. Additionally, it is of interest to students in urban planning, architecture and design, human geography, urban sociology, and related fields.
INTRODUCTION -- Chapter 1 Introducing Urban Alternatives -- PART 1 THINKING THE URBAN DIFFERENTLY -- Chapter 2 'Children of the Freeway': Overcoming Structure and Restriction in the Pursuit of Alternative Space -- Chapter 3 Reimagined Strategic Terrains of Urban Politics: Enabling Alternative Urban Futures -- Chapter 4 Spatial Dissensus: Spatial Self-Organisation at Wards Corner -- PART 2 GOVERNING THE URBAN DIFFERENTLY -- Chapter 5 Temporary Use: Sliding into Informality or Fostering Democratic Experimentation? -- Chapter 6 Alternative Spaces of Governance: Mobilising New Cultural Politics in Berlin -- Chapter 7 The Game of Participation in Amsterdam East: An Alternative to the Neoliberal or a Neoliberal Alternative? -- PART 3 PERFORMING AND PRODUCING THE URBAN DIFFERENTLY -- Chapter 8 Urban Alternatives Through Cooperation: Autonomous Geographies and Recreational Running in Sofia, Bulgaria -- Chapter 9 Alternative Spatial Styles: An Exploration of Sociospatial Youth Culture in Turin, Italy -- Chapter 10 Space and Temporality of Urban Alternatives: Lessons Learnt From Milanese Cases of Self-Organised Reappropriation of Abandoned Urban Spaces -- Chapter 11 Carving Enclaves of Alternative Urbanisms in Hong Kong -- Chapter 12 The Production of Space by an Esoteric Spiritual Community: The Case of Damanhur, Italy -- CONCLUSION -- Chapter 13 Enabling Alternative Urban Futures.
Keywords: Sociology, Urban; Human geography; Urban Sociology; Human Geography